東亞國家國民小學教師工作滿意度之相關因素研究： 以 TALIS 資料為例 The Related Factors of Teacher Job Satisfaction in Elementary Schools of East Asian Countries: Evidence from the TALIS Dataset - 張芳全 Fang-Chuan Chang (National Changhua University of Education, 2022)
本研究以 2018 年 OECD 的教與學國際調查資料探討臺灣、日本、韓國的國小教師工作滿意度因素，各以 3,441、3,062、3,058 名教師，透過迴歸分析獲得結論如下：學校教師團隊愈創新，愈認為教職可以影響學生，工作滿意度愈高；然而教師教育程度、教職是安定工作、教職可以幫助弱勢與工作滿意度沒有關聯。這三國的差異包括：1. 日本的女教師工作滿意度明顯低於男性，而臺韓則沒有差異。2. 臺日的教師年資愈長，工作滿意度愈低，韓國沒有關聯。3. 臺日的教師把教職作為首選，工作滿意度較高，而韓國沒有關聯。4. 日本的教師工作時間愈長，工作滿意度愈低，而臺韓則沒有關聯。5. 日本教師愈認為教職是可靠收入，工作滿意度愈低，而臺韓在此項沒有關聯。6. 臺灣的教師愈認為教職容易安排生活時間，工作滿意度較高；日本的教師認為在安排工作時間與工作滿意度為負向關聯。7. 臺日的教師愈認為教職可對社會貢獻，工作滿意度愈高，然而韓國的教師沒有關聯。本研究貢獻在於儒家文化圈的學校團隊創新和教職，與學生和工作滿意度是重要的關聯因素，並針對結論提出具體建議。 Based on the 2018 OECD's Teaching and Learning International Survey, the research explored factors related to the job satisfaction of elementary school teachers in Taiwan, Japan and South Korea with 3,441, 3,062, 3,058 teachers in the three countries respectively, and regression analysis was performed. The following conclusions were obtained. The more innovative the school teacher team of school teachers in the three countries, the more they believed that teaching positions can affect students, and the higher job satisfaction. However, the teacher's education level, teaching positions were stable jobs, and teaching positions can help the disadvantaged, and there was no significant correlation with job satisfaction. The differences in the three countries included: 1. The job satisfaction of female teachers in Japan was significantly lower than that of male teachers, while there was no significant difference between male and female teachers in Taiwan and South Korea. 2. The more senior teachers in Taiwan and Japan, the lower the job satisfaction, while South Korea had no significant correlation. 3. Teachers in Taiwan and Japan prioritized teaching positions and had higher job satisfaction, while South Korea had no significant correlation. 4. The longer the working week of Japanese teachers, the lower the job satisfaction. However, there was no significant correlation between the working hours and job satisfaction of teachers in Taiwan and South Korea respectively. 5. The more Japanese teachers thought that teaching was a reliable income, the lower their job satisfaction, while Taiwan and South Korea had no significant relationship. 6. Teachers in Taiwan thought that teaching posts were easier to arrange life time and had higher job satisfaction. Japanese teachers had a negative correlation with job satisfaction. 7. The more teachers in Taiwan and Japan believed that teachers can contribute to society, the higher their job satisfaction. However, teachers in South Korea were not significantly related to this variable. The contributions of the research lay in the Confucian cultural circle, and school team innovation and teaching positions can affect students, and job satisfaction was an important factor. An in-depth discussion of the results and specific suggestions were made.